2001
DOI: 10.1051/0004-6361:20010144
|View full text |Cite
|
Sign up to set email alerts
|

The O-Na and Mg-Al anticorrelations in turn-off and early subgiants in globular clusters

Abstract: Abstract. High dispersion spectra (R ∼ > 40 000) for a quite large number of stars at the main sequence turn-off and at the base of the giant branch in NGC 6397 and NGC 6752 were obtained with the UVES on Kueyen (VLT UT2). The [Fe/H] values we found are −2.03 ± 0.02 ± 0.04 and −1.42 ± 0.02 ± 0.04 for NGC 6397 and NGC 6752 respectively, where the first error bars refer to internal and the second ones to systematic errors (within the abundance scale defined by our analysis of 25 subdwarfs with good Hipparcos par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

59
583
6
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 524 publications
(649 citation statements)
references
References 40 publications
59
583
6
1
Order By: Relevance
“…Star identifications, Na, and Mg abundances in Table 3 come from Gratton et al (2001). In Table 4, identifications, atmosphere parameters and abundances other than S come from Carretta et al (2004), with the exception of star # 952, described in Bonifacio et al (2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Star identifications, Na, and Mg abundances in Table 3 come from Gratton et al (2001). In Table 4, identifications, atmosphere parameters and abundances other than S come from Carretta et al (2004), with the exception of star # 952, described in Bonifacio et al (2007).…”
Section: Resultsmentioning
confidence: 99%
“…The atmospheric parameters have been taken from Gratton et al (2001) for the stars in NGC 6752 and from Carretta et al (2004) and Bonifacio et al (2007) (for star # 952) for the stars in 47 Tuc. The 47 Tuc stars have a typical temperature of 5800 K for the TO stars (log g = 4.05) and of 5100 K for the subgiants (log g = 3.84).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The star-to-star abundance variations in C, N, O and Na have been observed in stars at or near the main-sequence turnoff (e.g., Gratton et al 2001;Ramírez & Cohen 2003), supporting the hypothesis that the GC stars did not produce their abundances in situ. Instead, a previous generation of stars polluted the atmospheres of stars we observe today or provided part of the material from which those stars formed (Cottrell & Da Costa 1981).…”
Section: Introductionmentioning
confidence: 53%
“…Hence, these abundance patterns are somehow the result of the cluster environment. The variations of the elements follow a similar pattern: C-N, O-Na and Mg-Al are anticorrelated (Shetrone 1996;Kraft et al 1997;Cannon et al 1998;Gratton et al 2001;Cohen & Meléndez 2005). Furthermore, Smith et al (2005) noted that stars in M4 showed evidence for a Na-F anticorrelation (an F spread was also found in NGC 6712; Yong et al 2008a), while Pasquini et al (2005) and Bonifacio et al (2007) found a Na-Li anticorrelation in NGC 6752 and 47 Tucanae, respectively.…”
Section: Introductionmentioning
confidence: 80%